3D reconstruction of ball trajectory from a single camera in the ball game - Shen, L.; Liu, Q.; Li, L.; Yue, H. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
The 3D ball trajectory provides us quantitative technical or tactical information (e.g. the ball speed of serve). The 3D trajectory can be reconstructed by multiple camera system or single camera system. The single camera 3D reconstruction method is better than the multiple camera one, because it is convenient for the video from television. The existing monocular 3D reconstruction method suffers from the model-drifting problem. We solve this problem using a new cost function. Experimental result shows that our method is more accurate than classical method, because our cost function is a mixture of the physical model and the geometric model.